Fluorine-containing polymer mixture for high moisture permeability and ultra-breathable microporous membrane and its application

By using a fluorine-containing polymer mixture to avoid flammable and explosive lubricants and preparing a highly moisture-permeable and ultra-breathable microporous membrane, the existing technology's problems of microporous membranes being susceptible to oil contamination and lubricating oil safety hazards are solved, achieving It has efficient waterproof and breathable performance and good oil resistance.

CN112980118BActive Publication Date: 2025-01-21SHANGHAI HYPROOF TECHNOLOGY CO LTD +1
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202110174835.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-02-07
Publication Date
2025-01-21
Estimated Expiration
2041-02-07

AI Technical Summary

Technical Problem

In the prior art, the expanded polytetrafluoroethylene microporous membrane is easily contaminated by oil and loses its waterproofness, and the lubricating oil is flammable and explosive during the deoiling process, which poses industrial safety risks. At the same time, the waterproof and breathable properties of existing products need to be improved, especially in aerospace and seafaring applications.

Method used

A fluorine-containing polymer mixture is used to obtain a composition through shear-free mixing. Component A is a blend of high molecular weight polytetrafluoroethylene homopolymer or copolymer dispersion resin and fluorine-containing ion exchange resin. Component B It is a fluorine-containing alkyl acrylate monomer with a molecular weight of less than 3,000. Component C is a polyurethane acrylate prepolymer with a molecular weight of less than 8,000. Component D is a high-temperature free radical initiator. The mixture is blended gently and without shear to avoid the use of flammable and explosive lubricants to prepare a highly moisture-permeable and ultra-breathable microporous membrane.

Benefits of technology

The preparation of highly moisture-permeable and ultra-breathable microporous membranes has been achieved. The initial moisture permeability is greater than 10,000g/m2/d, the air permeability is greater than 2mm/s under an air pressure difference of 300Pa, and the oil resistance is at least level 5, which can resist high water pressure and It prevents the intrusion of toxic and harmful liquids, has better air permeability and moisture permeability than existing technologies, and has good sealing effect at the seams.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The fluorine-containing polymer mixture for high moisture permeability and ultra-breathable microporous membrane is obtained by mixing a composition consisting of component A, component B, component C and component D in a non-shearing manner, wherein the mass content of each component is 50-90%, 3-25%, 0-35% and 0-3% in sequence; component A has a standard specific gravity of 2.13-2.18 g / m 3 A blend of a high molecular weight polytetrafluoroethylene homopolymer or copolymer dispersion resin and a fluorine-containing ion exchange resin, wherein the mass ratio of the fluorine-containing ion exchange resin to the high molecular weight polytetrafluoroethylene homopolymer or copolymer dispersion resin is 0.5 to 10:100; component B is a fluorine-containing alkyl acrylate monomer or a fluorine-containing alkyl methacrylate monomer or a mixture of the two with a molecular weight of less than 3000 and a melting point of less than 80°C; component C is a polyurethane acrylate prepolymer or a fluorine-free alkyl acrylate monomer or a mixture of the two with a molecular weight of less than 8000 and a melting point of less than 80°C; component D is a high temperature free radical initiator.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of polymer membrane materials, and specifically relates to a fluorine-containing polymer mixture for a highly moisture-permeable and ultra-breathable microporous membrane and its application. Background Art

[0002] Fluorine-containing polymers, especially tetrafluoroethylene homopolymers, modified or copolymer resins, are widely used in chemical materials, mechanical electronics, aerospace, military protection, new materials and new energy fields.

[0003] Expanded polytetrafluoroethylene is a fluorine-containing microporous polymer material with a highly microporous structure, excellent physical and chemical properties, mechanical properties, waterproof and breathable properties, and chemical stability. Since the 1970s, it has been used to manufacture wire and cable insulation materials, medical equipment, sealing materials, environmental protection filtration, and clothing fabrics. In industry, high-purity (>99.99%) tetrafluoroethylene monomers are usually used to prepare dispersed resins by dispersion polymerization or copolymerization. The materials used to prepare expanded polytetrafluoroethylene are generally ultra-high molecular weight and high crystallinity tetrafluoroethylene homopolymer dispersion or modified resins, usually through paste extrusion, extrusion, degreasing, and then unidirectional or bidirectional stretching, and finally shaping to make expanded fluorine-containing microporous membrane materials, but this kind of microporous membrane is easily contaminated by oil and loses its waterproofness. In addition, the lubricating oil used is flammable and explosive during the degreasing process, which is easy to cause industrial safety hazards. In the 1980s, the American Gore Company publicly invented that a hydrophilic polyurethane was coated on one side of the expanded polytetrafluoroethylene film to improve its oil resistance on one side, but the air permeability of the film was sacrificed. In the 1990s, the American company Gore invented the method of coating expanded polytetrafluoroethylene film with fluorinated acrylic emulsion to improve its oil resistance without sacrificing its air permeability. However, the manufacturing process of such a product is too complicated, and its waterproof and breathable properties need to be further improved, especially when it is used in aerospace and navigation, and its performance still has room for improvement.

[0004] Chinese patent document CN1373792A discloses a transparent elastomer composition obtained by co-coagulation of a fluororesin particle emulsion with an average particle size of 20 to 150 nanometers and an elastomer particle emulsion, wherein the fluororesin particles are uniformly dispersed in the elastomer. Since the fluororesin particles are uniformly dispersed in the elastomer in advance, an elastomer molded product with excellent mechanical strength, wear resistance and transparency can be provided. However, such an elastomer composition cannot be expanded to form a fluorine-containing microporous film because the fluororesin particle size is too small and the molecular weight is not high enough. To obtain an expanded fluorine-containing microporous material with high enough strength, the molecular weight of polytetrafluoroethylene must be high enough, the standard specific gravity of the general resin must be between 2.14 and 2.17, and the average particle size must be between 180 and 360 nanometers.

[0005] Chinese patent document CN104437126A discloses a method for preparing a super-hydrophobic polytetrafluoroethylene microporous membrane, a membrane obtained by the method and its application, and CN102294181A discloses a double-rejection polytetrafluoroethylene microporous membrane. Both works use polytetrafluoroethylene, a super-hydrophobic high molecular polymer (number average molecular weight 5000-250000) such as fluorinated alkyl acrylate, and a flammable and explosive lubricating oil to mix together to make a membrane. The obtained membrane has a low tensile strength of <20MPa and low oil resistance (only resistant to No. 3 oil), and the composite membrane fabric has poor anti-fouling and water washing resistance.

[0006] Chinese patent document CN103158310A discloses a highly oil-repellent and waterproof seamless polytetrafluoroethylene expanded sheet and a preparation method thereof. The film is made of polytetrafluoroethylene and flammable and explosive lubricating oil, and then a polyurethane resin coating is added for compounding. The obtained film has no air permeability and no oleophobicity (only resistant to No. 1 oil). The composite fabric has poor moisture permeability and is uncomfortable to wear.

[0007] Chinese patent document CN104760381A discloses a method for preparing polytetrafluoroethylene waterproof and breathable fabrics with enhanced breathability, which uses polytetrafluoroethylene and flammable and explosive lubricating oil to form a film, and then adds a microporous polyurethane coating. The resulting film has low air permeability, no oleophobicity (only resistant to No. 1 oil), poor flame retardancy, and is not suitable for high-end applications.

[0008] Chinese patent document CN107325238A discloses a fluorine-containing super-oleophobic microporous membrane and its application. The microporous membrane has good air permeability, but there is still room for improvement in moisture permeability.

[0009] Chinese patent document CN106977640A discloses a composite film filled with fluorine-containing and chlorine-containing conductive polymers on one side. The air permeability of the composite film is poor, and there is still room for improvement in moisture permeability. Summary of the invention

[0010] In order to solve at least one of the technical problems existing in the prior art mentioned above, on the one hand, the embodiment of the present application discloses a fluorine-containing polymer mixture for a highly moisture-permeable and ultra-breathable microporous membrane, wherein the fluorine-containing polymer mixture is obtained by mixing a composition consisting of component A, component B, component C and component D by shear-free mixing, wherein the mass content of each component is 50-90%, 3-25%, 0-35%, and 0-3% in sequence;

[0011] Component A has a standard specific gravity of 2.13 to 2.18 g / m 3 A blend of a high molecular weight polytetrafluoroethylene homopolymer or copolymer dispersion resin and a fluorine-containing ion exchange resin, wherein the mass ratio of the fluorine-containing ion exchange resin to the high molecular weight polytetrafluoroethylene homopolymer or copolymer dispersion resin is 0.5 to 10:100;

[0012] Component B is a fluorinated alkyl acrylate monomer or a fluorinated alkyl methacrylate monomer or a mixture of the two, having a molecular weight of less than 3000 and a melting point of less than 80°C;

[0013] Component C is a polyurethane acrylate prepolymer or a fluorine-free alkyl acrylate monomer or a mixture of the two having a molecular weight of less than 8000 and a melting point below 80°C;

[0014] Component D is a high temperature free radical initiator.

[0015] Further, in some embodiments, the fluorine-containing polymer mixture for high moisture permeability and ultra-breathable microporous membrane disclosed in the embodiments, the high molecular weight polyethylene homopolymer or copolymer dispersion resin is an ultra-high molecular weight polytetrafluoroethylene homopolymer or copolymer dispersion resin, and its standard specific gravity is 2.135-2.165 g / m 3 The melting point is between 325 and 350° C.; the fluorinated ion exchange resin is selected from any one of a fluorinated anion exchange resin, a fluorinated cation exchange resin, and a fluorinated dual ion exchange resin, or any combination thereof.

[0016] Some embodiments disclose a fluorinated polymer mixture for a highly moisture-permeable and ultra-breathable microporous membrane, wherein the polymer side chain of the fluorinated ion exchange resin contains an ion exchange group, and the fluorinated ion exchange resin includes any one of a fluorinated sulfonic acid resin, a fluorinated carboxylic acid resin, a fluorinated phosphoric acid resin, a fluorinated tertiary amine resin, and a fluorinated quaternary amine resin, or any combination thereof; and the fluorinated monomer of the fluorinated ion exchange resin is selected from any one of tetrafluoroethylene, vinylidene fluoride, trifluoroethylene, and vinyl fluoride, or any combination thereof.

[0017] In some embodiments, the fluorine-containing polymer mixture for high moisture permeability and ultra-breathable microporous membrane disclosed has component A, component B, component C and component D having mass contents of 65-80%, 6-15%, 2-23% and 0-2% respectively.

[0018] Some embodiments disclose a fluorine-containing polymer mixture for a highly moisture-permeable and ultra-breathable microporous membrane, wherein component B includes: perfluorobutyl ethyl acrylate, perfluorobutyl ethyl methacrylate, perfluorohexyl ethyl acrylate, perfluorohexyl ethyl methacrylate, perfluorooctyl ethyl acrylate, perfluorooctyl ethyl methacrylate, N-methyl perfluorobutyl sulfonyl amino ethyl acrylate, N-methyl perfluorobutyl sulfonyl amino ethyl methacrylate, N-methyl perfluorohexyl sulfonyl amino ethyl acrylate, N-methyl perfluorohexyl sulfonyl amino ethyl methacrylate, N-methyl perfluorooctane sulfonyl amino ethyl acrylate, N-methyl perfluorooctane sulfonyl amino ethyl methacrylate, and other C5-C16 fluorinated alkyl acrylates or methacrylates.

[0019] In some embodiments, the fluorine-containing polymer mixture for high moisture permeability and ultra-breathable microporous membrane disclosed in the invention is a polyurethane acrylate prepolymer that is hot-melt and has a melting point of less than 80° C. The raw materials for its preparation include:

[0020] Aromatic diisocyanate, aliphatic diisocyanate or diisocyanate or triisocyanate;

[0021] Polyols with molecular weight between 600 and 5000;

[0022] The polyol includes polyethylene glycol, polypropylene glycol, polybutylene glycol, polyester polyol or polycarbonate polyol.

[0023] Some embodiments disclose a method for preparing a fluorine-containing polymer mixture and a polyurethane acrylate prepolymer for a high moisture permeability and ultra-breathable microporous membrane, including:

[0024] The reactor was evacuated to remove moisture, diisocyanate was added, the temperature was raised, and stirring was started;

[0025] The temperature in the reaction kettle rises to 50-150°C, and polyol is introduced into the kettle, and the reaction is carried out for 10-180 minutes; the polyol is a polyether polyol or a polyester polyol, wherein the molar ratio of diisocyanate to polyol is 2:1-8:1;

[0026] Add hydroxyalkyl acrylate or hydroxyalkyl methacrylate into the reaction kettle to completely react with the unreacted isocyanate by hydroxyalkyl, maintain the reaction temperature at 50-150°C, react for 10-180 minutes, cool and discharge the material, and obtain a polyurethane acrylate prepolymer; wherein the molar number of the added hydroxyalkyl acrylate or hydroxyalkyl methacrylate is greater than or equal to the molar number of the unreacted isocyanate.

[0027] In some embodiments, the fluorine-containing polymer mixture for high moisture permeability and super breathable microporous membrane disclosed in the invention comprises a fluorine-free alkyl acrylate as a monomer capable of free radical polymerization or a mixed monomer thereof, specifically comprising: hydroxyalkyl acrylate, hydroxyalkyl methacrylate, C5-C20 alkyl acrylate, C4-C20 alkyl methacrylate, and C6-C20 vinyl ester; wherein the hydroxyalkyl acrylate comprises hydroxyethyl acrylate or hydroxypropyl acrylate, and the hydroxyalkyl methacrylate comprises hydroxyethyl methacrylate or hydroxypropyl methacrylate.

[0028] Some embodiments disclose a fluorine-containing polymer mixture for a high moisture permeability and high air permeability microporous membrane, wherein the half-life of the high temperature free radical initiator is between 100 and 250 degrees, and specifically includes diisopropylbenzene peroxide, 2,5-dimethyl-2,5-bis-tert-butylperoxyhexane, di-tert-butyl peroxide, 2,5-dimethyl-2,5-bis-tert-butylperoxide-3-hexyne, and isopropylbenzene hydroperoxide.

[0029] On the other hand, some embodiments disclose the use of a fluorine-containing polymer mixture for a high moisture permeability and high air permeability microporous membrane. The fluorine-containing polymer mixture is used to prepare a high moisture permeability and super air permeable microporous membrane. The preparation method specifically includes:

[0030] Component A, component B, component C and component D are mixed in a set ratio, and blended for a first set time by a gentle non-shearing method to obtain a fluorine-containing polymer mixture;

[0031] Pre-pressing the fluorine-containing polymer mixture into a cylindrical paste mixture;

[0032] Extruding the paste mixture into a rod shape at a first set temperature, and then rolling it into a ribbon-shaped mixture;

[0033] The strip-shaped mixed material is quickly stretched longitudinally at a second set temperature, then quickly stretched transversely at a third set temperature, and finally fixed at a fourth set temperature for a second set time, thereby obtaining a highly moisture-permeable and ultra-breathable microporous membrane.

[0034] Further, some embodiments disclose a composite material prepared from a high moisture permeability super breathable microporous membrane prepared from a fluorine-containing polymer mixture, wherein the composite material is obtained by point-bonding a high moisture permeability super breathable microporous membrane with a textile fabric, wherein the textile fabric is a knitted fabric or a non-woven fabric, and the surface density is 20 to 180 g / m 2 The initial water pressure resistance of the high moisture permeability and ultra-breathable microporous membrane composite material is greater than 100kPa. After washing 10 times, the water pressure resistance is still greater than 60kPa; the moisture permeability is greater than 8000g / m 2 / d, the air permeability is greater than 1mm / s under 300Pa air pressure difference; after the composite material is dry-bent 10,000 times at -40℃, the water pressure resistance is greater than 70kPa.

[0035] The fluorine-containing polymer mixture disclosed in the embodiment of the present application is obtained by mixing a composition consisting of component A, component B, component C and component D by non-shear mixing, wherein the mass content of each component is 50-90%, 3-25%, 0-35%, 0-3% in sequence, and component A has a standard specific gravity of 2.13-2.18 g / m 3 A blend of a high molecular weight polytetrafluoroethylene homopolymer or copolymer dispersion resin and a fluorine-containing ion exchange resin, wherein the mass ratio of the fluorine-containing ion exchange resin to the high molecular weight polytetrafluoroethylene homopolymer or copolymer dispersion resin is 0.5 to 10:100; the fluorine-containing ion exchange resin can effectively improve the moisture permeability of the microporous membrane prepared by the fluorine-containing polymer mixture without damaging its waterproof performance, and the initial moisture permeability of the high moisture permeability super breathable microporous membrane prepared by the fluorine-containing polymer mixture is greater than 10000g / m 2 / d, the air permeability is greater than 2mm / s under 300Pa air pressure difference, the initial oil resistance is at least level 5, it can resist high water pressure, and can prevent toxic and harmful liquids from invading the human body, its air permeability and moisture permeability are better than the existing technology, and the sealing effect at the sewing line is good. High moisture permeability super breathable microporous membrane composite material has high water pressure resistance, high air permeability and high moisture permeability, and has good protection against penetrating toxic and harmful liquids. The protective clothing made of high moisture permeability super breathable microporous membrane composite material is light, comfortable, warm, and has excellent protective performance, which can greatly improve the protective combat capability of operators. DETAILED DESCRIPTION

[0036] The word "embodiment" used here as an "exemplary" does not necessarily mean that any embodiment described is superior to or better than other embodiments. Unless otherwise specified, the performance index tests in the embodiments of this application are performed using conventional test methods in the art. It should be understood that the terms described in this application are only used to describe specific implementation methods and are not used to limit the content disclosed in this application.

[0037] Unless otherwise specified, the technical and scientific terms used in this document have the same meanings as commonly understood by ordinary technicians in the technical field to which this application belongs; other experimental methods and technical means not specifically specified in this application refer to experimental methods and technical means commonly used by ordinary technicians in this field.

[0038] The terms "substantially" and "approximately" used herein are used to describe small fluctuations. For example, they can refer to less than or equal to ±5%, such as less than or equal to ±2%, such as less than or equal to ±1%, such as less than or equal to ±0.5%, such as less than or equal to ±0.2%, such as less than or equal to ±0.1%, such as less than or equal to ±0.05%. The numerical data represented or presented in the range format herein are used only for convenience and brevity, and should therefore be flexibly interpreted as including not only the values ​​clearly listed as the limits of the range, but also all independent values ​​or sub-ranges contained in the range. For example, the numerical range of "1-5%" should be interpreted as including not only the clearly listed values ​​of 1% to 5%, but also the independent values ​​and sub-ranges within the range shown. Therefore, independent values ​​such as 2%, 3.5% and 4% and sub-ranges such as 1%-3%, 2%-4% and 3%-5% are included in this numerical range. This principle also applies to the range of only one numerical value. In addition, such an interpretation applies regardless of the width of the range or the characteristics described. The moisture permeability test adopts the national standard GB / T 12704.1-2009 (calcium chloride, positive cup method); the air permeability test adopts the national standard GB / T 5453-1997 test method; the oil resistance test adopts the American standard AATCC118-2002 test method.

[0039] In this document, including the claims, all conjunctions such as "comprises", "includes", "with", "having", "containing", "involving", "accommodating", etc. are understood to be open, that is, meaning "including but not limited to". Only the conjunctions "consisting of" and "composed of" are closed conjunctions.

[0040] In order to better illustrate the content of the present application, numerous specific details are provided in the specific examples below. It should be understood by those skilled in the art that the present application can also be implemented without certain specific details. In the embodiments, some methods, means, instruments, equipment, etc. well known to those skilled in the art are not described in detail in order to highlight the main purpose of the present application.

[0041] Under the premise of no conflict, the technical features disclosed in the embodiments of the present application can be combined arbitrarily, and the resulting technical solutions belong to the contents disclosed in the embodiments of the present application.

[0042] In some embodiments, the fluorine-containing polymer mixture for the high moisture permeability and ultra-breathable microporous membrane is a white opaque mixture, which is obtained by mixing a composition consisting of component A, component B, component C and component D without shearing; wherein the mass content of each component is 50-90%, 3-25%, 0-35%, and 0-3% respectively; component A has a standard specific gravity of 2.13-2.18 g / m 3 A blend of a high molecular weight polytetrafluoroethylene homopolymer or copolymer dispersion resin and a fluorine-containing ion exchange resin, wherein the mass ratio of the fluorine-containing ion exchange resin to the high molecular weight polytetrafluoroethylene homopolymer or copolymer dispersion resin is 0.5-10:100; component B is a fluorine-containing alkyl acrylate monomer or a fluorine-containing alkyl methacrylate monomer or a mixture of the two with a molecular weight of less than 3000 and a melting point of less than 80°C; component C is a polyurethane acrylate prepolymer or a fluorine-free alkyl acrylate monomer or a mixture of the two with a molecular weight of less than 8000 and a melting point of less than 80°C; component D is a high temperature free radical initiator.

[0043] As an optional embodiment, the high molecular weight polyethylene homopolymer or copolymer dispersion resin is an ultra-high molecular weight polytetrafluoroethylene homopolymer or copolymer dispersion resin, and its standard specific gravity is 2.135 to 2.165 g / m 3 The melting point is between 325 and 350° C.; the fluorinated ion exchange resin is selected from any one of a fluorinated anion exchange resin, a fluorinated cation exchange resin, and a fluorinated dual ion exchange resin, or any combination thereof.

[0044] As an optional embodiment, the preparation method of high molecular weight polytetrafluoroethylene homopolymer or copolymer dispersion resin comprises:

[0045] Deionized water and surfactant are added to the autoclave, vacuumed and deoxygenated, heated, and stirred; as an optional embodiment, the surfactant is an organic substance containing 6 to 16 carbon atoms and at least one carboxylic acid or sulfonic acid functional group; the preferred surfactant is a perfluorinated surfactant;

[0046] When the temperature in the reactor rises to 50-80° C., tetrafluoroethylene with a purity greater than 99.999% and other optional comonomers are introduced; wherein the comonomer is selected from any one of perfluoromethyl vinyl ether, perfluoroethyl vinyl ether, perfluoropropyl vinyl ether, vinylidene fluoride, vinyl fluoride, 3,3,3-trifluoropropylene, perfluoro C2-C8 alkylethylene, or any combination thereof, and the volume content of tetrafluoroethylene in the reactor is usually 95-99.99%;

[0047] After the pressure in the reactor reaches 1.1-2.9Mpa, a free radical initiator is added to start the polymerization reaction, and the temperature in the reactor is maintained at 70-110°C; as an optional embodiment, the free radical initiator is any one or any combination of sulfate, hydrogen peroxide or organic peroxide; as a more preferred embodiment, the pressure in the reactor is maintained above 1.5Mpa during the polymerization reaction;

[0048] The reaction is continued until the solid content of the emulsion reaches 20-39%. After the temperature in the kettle is lowered to below 50°C, stirring is stopped, unreacted monomers are discharged, and reactants are discharged to obtain an ultra-high molecular weight tetrafluoroethylene homopolymer or copolymer dispersed resin emulsion, the average particle size of the primary particles of which is 180-390nm; preferably, the average particle size of the primary particles is 220-330nm.

[0049] Usually, ultra-high molecular weight tetrafluoroethylene homopolymer or copolymer dispersion resin emulsion is condensed and dried to obtain ultra-high molecular weight tetrafluoroethylene homopolymer or copolymer dispersion resin.

[0050] The fluorinated ion exchange resin is usually used in the form of a fluorinated ion exchange resin dispersion to facilitate uniform mixing.

[0051] As an optional embodiment, the polymer side chain of the fluorinated ion exchange resin contains ion exchange groups, and the fluorinated ion exchange resin includes any one of a fluorinated sulfonic acid resin, a fluorinated carboxylic acid resin, a fluorinated phosphoric acid resin, a fluorinated tertiary amine resin, and a fluorinated quaternary amine resin, or any combination thereof; and the fluorinated monomer of the fluorinated ion exchange resin is selected from any one of tetrafluoroethylene, vinylidene fluoride, trifluoroethylene, and vinyl fluoride, or any combination thereof.

[0052] As an optional embodiment, the mass contents of component A, component B, component C and component D constituting the fluorine-containing polymer mixture are 65-80%, 6-15%, 2-23% and 0-2% respectively.

[0053] As an optional embodiment, component B of the fluorine-containing polymer mixture includes: perfluorobutyl ethyl acrylate CH2=CHCOOC2H4C4F9, perfluorobutyl ethyl methacrylate CH2=CCH3COOC2H4C4F9, perfluorohexyl ethyl acrylate CH2=CHCOOC2H4C6F 13 , Perfluorohexylethyl methacrylate CH2=CCH3COOC2H4C6F 13 , Perfluorooctylethyl acrylate CH2=CHCOOC2H4C8F 17 , Perfluorooctylethyl methacrylate CH2=CCH3COOC2H4C8F 17 、N-methyl perfluorobutyl sulfonyl amino ethyl acrylate CH2=CHCOOC2H4NCH3SO2C4F9、N-methyl perfluorobutyl sulfonyl amino ethyl methacrylate CH2=CCH3COOC2H4NCH3SO2C4F9、N-methyl perfluorohexyl sulfonyl amino ethyl acrylate CH2=CHCOOC2H4NCH3SO2C6F 13 、N-methylperfluorohexylsulfonylaminoethyl methacrylate CH2=CCH3COOC2H4NCH3SO2C6F 13 、N-methyl perfluorooctanesulfonic acid ethyl acrylate CH2=CHCOOC2H4NCH3SO2C8F 17 、N-methyl perfluorooctanesulfonic acid aminoethyl methacrylate CH2=CCH3COOC2H4NCH3SO2C8F 17 , other C5-C16 fluorinated alkyl acrylates or methacrylates.

[0054] As an optional embodiment, the molecular weight of the fluorinated alkyl acrylate monomer or the fluorinated alkyl methacrylate monomer or the mixture of the two in component B is less than 2,000.

[0055] As an optional embodiment, the polyurethane acrylate prepolymer is hot-melt, and its melting point is less than 80° C. The raw materials for its preparation include:

[0056] Aromatic diisocyanate, aliphatic diisocyanate or diisocyanate or triisocyanate;

[0057] Polyols with molecular weight between 600 and 5000;

[0058] The polyol includes polyethylene glycol, polypropylene glycol, polybutylene glycol, polyester polyol or polycarbonate polyol.

[0059] As an optional embodiment, the preparation method of the polyurethane acrylate prepolymer includes:

[0060] The reactor was evacuated to remove moisture, diisocyanate was added, the temperature was raised, and stirring was performed;

[0061] The temperature in the reaction kettle rises to 50-150°C, and polyol is introduced into the kettle, and the reaction is carried out for 10-180 minutes; the polyol is a polyether polyol or a polyester polyol, wherein the molar ratio of diisocyanate to polyol is 2:1-8:1;

[0062] Add hydroxyalkyl acrylate or hydroxyalkyl methacrylate into the reaction kettle to completely react with the unreacted isocyanate by hydroxyalkyl, maintain the reaction temperature at 50-150°C, react for 10-180 minutes, cool and discharge the material, and obtain a polyurethane acrylate prepolymer; wherein the molar number of the added hydroxyalkyl acrylate or hydroxyalkyl methacrylate is greater than or equal to the molar number of the unreacted isocyanate.

[0063] As a more preferred embodiment, the melting point of the fluorinated alkyl acrylate monomer or the fluorinated alkyl methacrylate monomer or the mixture thereof is less than 50°C.

[0064] As an optional embodiment, the molecular weight of the polyol is between 600 and 5000.

[0065] As a more preferred embodiment, the molecular weight of the polyol is between 1000 and 3000, and each polyol molecule contains 2 to 3 hydroxyl groups.

[0066] As a more preferred embodiment, the molecular weight of component C, the polyurethane acrylate prepolymer or the fluorine-free alkyl acrylate monomer or the mixture of the two is less than 5,000.

[0067] As a more preferred embodiment, the melting point of component C polyurethane acrylate prepolymer or fluorine-free alkyl acrylate monomer or a mixture of the two is less than 50°C.

[0068] As an optional embodiment, in the mixture of component C, polyurethane acrylate prepolymer and fluorine-free alkyl acrylate monomer, the mass content of polyurethane acrylate prepolymer is 0-70%, and the mass content of fluorine-free alkyl acrylate monomer is 30-100%.

[0069] As an optional embodiment, the fluorine-free alkyl acrylate has an average molecular weight of less than 1000 and a melting point of less than 80°C.

[0070] As a more preferred embodiment, the fluorine-free alkyl acrylate has an average molecular weight of less than 600, a melting point of greater than 50° C., and a boiling point of greater than 160° C. at normal pressure.

[0071] As an optional embodiment, the fluorine-free alkyl acrylate is a free radical polymerizable monomer or a mixed monomer thereof, specifically including: hydroxyalkyl acrylate, hydroxyalkyl methacrylate, C5-C20 alkyl acrylate, C4-C20 alkyl methacrylate, and C6-C20 vinyl ester; wherein the hydroxyalkyl acrylate includes hydroxyethyl acrylate or hydroxypropyl acrylate, the hydroxyalkyl methacrylate includes hydroxyethyl methacrylate or hydroxypropyl methacrylate, or any combination thereof.

[0072] As an optional embodiment, as an optional embodiment, the fluorine-free alkyl acrylate is a free radical polymerizable monomer or a mixed monomer thereof, having a boiling point greater than 200°C at normal pressure, including isooctyl acrylate, isononyl acrylate, isodecyl acrylate, isoundecyl acrylate, isonoundecyl acrylate, isotridecanyl acrylate, vinyl isooctanoate, vinyl neononanoate, vinyl neodecanoate, other C6-C18 alkyl acrylates, other C6-C18 alkyl methacrylates, or any combination thereof.

[0073] As an optional embodiment, the high temperature free radical initiator is an organic free radical initiator, and its half-life is between 100 and 250 degrees. The half-life mentioned in this article generally refers to the free radical initiator retaining at least half of the effective components that can generate free radicals after 10 hours at a certain temperature. Usually, high temperature free radical initiators include diisopropylbenzene peroxide (CAS: 80-43-3), 2,5-dimethyl-2,5-bis-(tert-butylperoxy)hexane (CAS: 78-63-7), di-tert-butyl peroxide (CAS: 110-05-4), 2,5-dimethyl-2,5-bis(tert-butylperoxy)-3-hexyne (CAS: 1068-27-5), and isopropylbenzene hydroperoxide (CAS: 80-15-9).

[0074] In some embodiments, the method of applying the fluorine-containing polymer mixture to prepare a highly moisture-permeable and ultra-breathable microporous membrane comprises:

[0075] (1) mixing an ultra-high molecular weight polytetrafluoroethylene homopolymer or copolymer dispersed resin powder with a fluorine-containing ion exchange resin dispersed solution, stirring without shearing, mixing thoroughly and evenly, and then placing in an oven or a vacuum oven to remove volatile substances, thereby obtaining component A;

[0076] (2) uniformly stirring the obtained component A, component B, component C, and component D in a non-shearing manner, directly pouring them into a preform pressing barrel, exhausting the air, and pressing the preforms at 20 to 100° C. to form cylindrical paste-like preforms; wherein no lubricating oil is added to avoid the danger of flammability and explosion during de-oiling;

[0077] (3) extruding the paste mixture through a push press at 20-100° C., and then calendering the extrudate into strips with a thickness of 50-2000 μm, preferably 80-800 μm;

[0078] (4) The strip is stretched uniaxially or biaxially at 100° C. to 200° C., and heat-set at 200° C. to 390° C. to obtain a highly moisture-permeable and ultra-breathable microporous membrane.

[0079] The high moisture permeability and ultra-breathable microporous membrane made of fluorine-containing polymer mixture has a thickness of 0.005-1.5mm and a surface density of 1-1200g / m 2 , porosity is 30-95%, tensile strength is greater than 20Mpa; initial oil resistance is at least level 5, moisture permeability is greater than 10000g / m 2 / d, the air permeability is greater than 2mm / s under 300Pa air pressure difference; after washing 10 times, the oil resistance is at least level 4, and the moisture permeability is greater than 9000g / m 2 / d, and the air permeability is greater than 1.5mm / s under 300Pa air pressure difference.

[0080] As a more preferred embodiment, the thickness of the high moisture permeability super breathable microporous membrane is 0.01 to 0.08 mm, and the surface density is 3 to 30 g / m 2 The porosity is 70-90%, the tensile strength is greater than 30MPa, the initial oil resistance is at least level 6; after washing 10 times, the oil resistance is at least level 5, and the moisture permeability is greater than 10000g / m 2 / d, and the air permeability is greater than 2mm / s under 300Pa air pressure difference.

[0081] Some embodiments disclose a high moisture permeability super breathable microporous membrane composite material, which is obtained by point-bonding a high moisture permeability super breathable microporous membrane and a textile fabric, wherein the textile fabric is a knitted fabric or a non-woven fabric, and the surface density is 20 to 180 g / m 2 The initial water pressure resistance of the high moisture permeability and ultra-breathable microporous membrane composite material is greater than 100kPa. After washing 10 times, the water pressure resistance is still greater than 60kPa; the moisture permeability is greater than 8000g / m 2 / d, the air permeability is greater than 1mm / s under 300Pa air pressure difference; after the composite material is dry-bent 10,000 times at -40℃, the water pressure resistance is greater than 70kPa. Usually the composite material is a composite fabric used to make special protective clothing. The composite material is compounded with a high moisture permeability and ultra-breathable microporous membrane of a point-bonded adhesive and a textile fabric to obtain a composite fabric.

[0082] As a more preferred embodiment, the initial water pressure resistance of the high moisture permeability and ultra-breathable microporous membrane composite material is greater than 200 kPa; after being washed 10 times, the water pressure resistance is greater than 100 kPa, and the moisture permeability is greater than 10000 g / m 2 / d, air permeability is greater than 2mm / s under 300Pa air pressure difference. The sealing effect is better after the water stop strip is attached to the sewing line.

[0083] In the examples herein, the performance of the high moisture permeability super breathable microporous membrane and the high moisture permeability super breathable microporous membrane composite material prepared by the fluorine-containing polymer mixture is tested, and the test methods involved include:

[0084] (1) The water pressure resistance of highly moisture permeable and ultra-breathable microporous membranes and their composite materials was tested using the FZ / T01004-2008 method, with the outer layer facing the water and the initial water pressure greater than 100 kPa;

[0085] (2) Wash with water in a standard washing machine, add detergent, and dry, repeat 10 times, and the performance requirement is that the water pressure resistance is greater than 100 kPa;

[0086] (3) Spray mosquito repellent N,N-diethyl-3-methylbenzamide (CAS#134-62-3)>95% on the cloth, cover it for 3 hours and measure the water pressure, which is required to be greater than 70 kPa;

[0087] (4) Spray the cloth with mosquito repellent, cover it for one day, wash it with water (add detergent) and dry it three times, and then measure the water pressure, which should be greater than 70 kPa;

[0088] (5) Moisture resistance: Wash 50 times in a standard washing machine without detergent, and then dry. The water pressure is measured and is required to be greater than 70 kPa.

[0089] (6) Low temperature resistance: the composite fabric is bent 10,000 times at -40°C and the water pressure is measured, which is required to be greater than 70 kPa;

[0090] (7) The air permeability of composite materials is tested in accordance with GB / T5453-1997, with the outer layer facing downward, and the speed is required to be less than 1 mm / s. The faster the speed, the better the air permeability.

[0091] (8) The moisture permeability of composite materials is tested according to the positive cup method of GB / T12704.1-2009; the outer layer fabric faces upwards, and the water vapor permeability is required to be greater than 8000g / m 2 / d. The greater the moisture permeability, the easier it is to discharge sweat vapor;

[0092] (9) The moisture permeability of composite materials is tested according to the inverted cup method of GB / T12704.1-2009, with the outer layer facing upwards, and the water vapor permeability is required to be greater than 10,000 g / m 2 / d, the bigger the better, and it is easier to discharge sweat.

[0093] The technical details are further described below in conjunction with embodiments.

[0094] Preparation of component A

[0095] Example 1

[0096] High molecular weight polytetrafluoroethylene copolymer dispersion resin

[0097] It is prepared by using tetrafluoroethylene and perfluoroethyl vinyl ether as polymerization monomers and ammonium sulfate as initiator. The preparation method comprises: firstly adding 500L of deionized water, 20Kg of high-purity paraffin with a melting point of 50°C to 85°C and 180g of ammonium perfluorooctanoate into a horizontal high-pressure reactor with a volume of about 1000L, evacuating the reactor to remove oxygen until the oxygen content is less than 20ppm, heating and stirring; when the temperature in the reactor rises to about 70°C, introducing tetrafluoroethylene gas with a purity greater than 99.999% into the reactor to make the pressure in the reactor reach about 2.2MPa; then adding 300g of perfluoroethyl vinyl ether C2F5-OCF=CF2 with a purity greater than 98% as a copolymer monomer into the reactor at a speed of 10g / min, and simultaneously adding 0.8g of ammonium persulfate dissolved in 500ml of water in advance as an initiator, starting a copolymerization reaction, maintaining the temperature in the reactor at 80-100°C, and introducing tetrafluoroethylene gas into the reactor during the reaction to maintain the pressure in the reactor at about 2.0MPa. Continue the reaction until the solid content of the emulsion reaches about 30%, then reduce the temperature in the kettle to below 50°C, stop stirring, discharge the unreacted monomers, reduce the pressure, discharge the reactants, and obtain an ultra-high molecular weight polytetrafluoroethylene copolymer dispersion resin emulsion, the average particle size of which is about 280nm. The emulsion is diluted and stirred at high speed to coagulate and demulsify, and the suspended polymer is placed on a plate and placed in an oven at 190°C for drying to obtain a high molecular weight polytetrafluoroethylene copolymer dispersion resin. After testing, the standard specific gravity of the high molecular weight tetrafluoroethylene copolymer dispersion resin is about 2.149g / m 3 , the melting point peak is between 325 and 350°C.

[0098] Fluoride ion exchange resin

[0099] The preparation method comprises: adding 39000g of pure water and 100g of ammonium perfluorooctanoate at room temperature into a closed pre-emulsification reactor A with a volume of about 100 liters, and stirring at high speed, and then slowly adding 5000g of fluorine-containing sulfonyl fluoride liquid phase monomer into the reactor A, wherein the fluorine-containing sulfonyl fluoride liquid phase monomer is formed by mixing 70% by mass of CF2=CF-OCF2CFCF3-O-CF2CF2-SO2F and 30% by mass of CF2=CF-O-CF2CF2-SO2F; Continue high-speed shear stirring for about 30 minutes to obtain a prepolymer emulsion; in another reactor B with a volume of about 100 liters, first exhaust oxygen until the oxygen content in the reactor is less than 20 ppm, then add all the prepolymer emulsion from reactor A, and introduce a gaseous mixed monomer into reactor B, which consists of 90% tetrafluoroethylene and 10% chlorotrifluoroethylene in a molar ratio. The temperature is raised to 70°C, the pressure in the reactor is maintained at 1.1 MPa, and 2.5 g of ammonium persulfate pre-dissolved in 1 L of deionized water is added to start free radical polymerization. The total weight ratio of the fluorine-containing sulfonyl fluoride liquid phase monomer and the gas phase mixed monomer actually participating in the free radical polymerization reaction is about 4:5; the mass ratio of the total weight of the free radical initiator to the fluorine-containing sulfonyl fluoride liquid phase monomer is 0.05%; the reaction temperature is controlled at 70-75°C, the reaction is carried out for 1 hour, the temperature in the kettle is lowered to room temperature, and the stirring is stopped to obtain a fluorine-containing chlorine-containing conductive polymer emulsion, the average particle size of its primary particles is about 100nm, and the solid content in the emulsion is about 19%. The obtained fluorine-containing chlorine-containing conductive polymer emulsion is hydrolyzed with sulfonyl fluoride-SO2F to obtain a fluorine-containing chlorine-containing sulfonic acid-SO3H conductive polymer, after drying, its specific gravity is about 1.99, the acid equivalent number (meq / g) is about 900, and the room temperature conductivity of its single film is>0.15S / cm. The fluorine-containing chlorine-containing sulfonic acid conductive polymer is heated to 60°C in 75% medical alcohol to dissolve, and a fluorine-containing ion exchange resin alcohol solution with a solid content of about 20% is obtained.

[0100] Preparation of component A

[0101] The high molecular weight polytetrafluoroethylene copolymer dispersion resin prepared in Example 1 was blended with the fluorine-containing ion exchange resin alcohol solution, and blended for half an hour in a gentle, shear-free manner to obtain a white opaque mixture, which was dried in a vacuum oven at 50° C. for 12 hours to remove the alcohol, thereby obtaining component A1; wherein the ratio of the fluorine-containing ion exchange resin to the high molecular weight polytetrafluoroethylene copolymer was 0.5:100.

[0102] Example 2

[0103] Component A2 was prepared by referring to the method of Example 1, wherein the ratio of the fluorine-containing ion exchange resin to the high molecular weight polytetrafluoroethylene copolymer was 5:100.

[0104] Example 3

[0105] Component A3 was prepared by referring to the method of Example 1, wherein the ratio of the fluorine-containing ion exchange resin to the high molecular weight polytetrafluoroethylene copolymer was 10:100.

[0106] Comparative Example 1

[0107] Referring to the method of Example 1, component A'1 was prepared, wherein the content of the fluorine-containing ion exchange resin was 0.

[0108] Comparative Example 2

[0109] Component A'2 was prepared by referring to the method of Example 1, wherein the ratio of the fluorine-containing ion exchange resin to the high molecular weight polytetrafluoroethylene copolymer was 15:100.

[0110] Preparation of component C

[0111] Example 4

[0112] Mixture of polyurethane acrylate prepolymer and fluorine-free alkyl acrylate

[0113] The polyurethane acrylate prepolymer is prepared by the following method, which specifically includes: in a reaction kettle with a volume of about 200L, the jacket is first heated to 100°C, the reaction kettle is vacuumed and flushed with nitrogen for dehumidification, 26.2Kg of 4,4'-dicyclohexylmethane diisocyanate HMDI containing about 200mol-NCO isocyanate is added, stirred, the temperature in the kettle is raised to about 100°C, and then 60Kg of polypropylene glycol with a molecular weight of about 2000 is added to the kettle, which contains about 60mol-OH hydroxyl groups, after reacting for about 90min, 18.2Kg of hydroxyethyl methacrylate containing about 140mol-OH hydroxyl groups is added, the temperature in the kettle is maintained at about 100°C, and the reaction is carried out for about 1 hour to obtain a polyurethane acrylate prepolymer with a viscous liquid and a melting point below 50°C.

[0114] In a stirring barrel with a volume of about 100 liters, 15 kg of the polyurethane acrylate prepolymer prepared in Example 4 was added at room temperature and pressure, and then 35 kg of isodecyl acrylate (CAS: 1330-61-6) was added, and the mixture was continuously stirred into a homogeneous phase. The stirring was stopped and the mixture was discharged to obtain a mixture of polyurethane acrylate prepolymer and fluorine-free alkyl acrylate in a mass ratio of 3:7, which was marked as component C1.

[0115] Example 5

[0116] Referring to the method of Example 4, a mixture of polyurethane acrylate prepolymer and non-fluorinated alkyl acrylate was prepared;

[0117] In a mixing barrel with a volume of about 100 liters, 25 kg of polyurethane acrylate prepolymer was added at room temperature and pressure, and then 25 kg of isodecyl acrylate (CAS: 1330-61-6) was added, and the mixture was continuously stirred into a homogeneous phase. The stirring was stopped and the mixture was discharged. The mass ratio of the polyurethane acrylate prepolymer to the fluorine-free alkyl acrylate was 5:5, which was marked as component C2.

[0118] Preparation of Fluorine-Containing Polymer Mixture

[0119] Example 6

[0120] Component A2 obtained in Example 2, the perfluoroalkyl ethyl acrylate mixture, component C1 obtained in Example 4, and cumene hydroperoxide were mixed in a mass ratio of 75:10:14:1, and blended for about half an hour using a gentle non-shearing method to obtain a fluorine-containing polymer mixture having a standard specific gravity of about 1.88 g / cm 3 , wherein the average molecular weight of the perfluoroalkyl ethyl acrylate mixture is less than 1000, and the melting point is less than 35°C; the distribution of the perfluoroalkyl group is 10% C4, 30% C6, 50% C8, 10% C10; and the cumene peroxide is CAS: 80-15-9. The fluorine-containing polymer mixture obtained in Example 6 is marked as mixture E1.

[0121] Comparative Example 3

[0122] Referring to the method of Example 6, a fluorine-containing polymer mixture is prepared, wherein component A is component A'1 obtained in Comparative Example 1; the standard specific gravity of the fluorine-containing polymer mixture obtained in Comparative Example 3 is about 1.89 g / cm 3 , marked as E'1.

[0123] Example 7

[0124] Component A1 obtained in Example 1, a mixture of perfluoroalkyl ethyl acrylates, and cumene hydroperoxide (CAS: 80-15-9) were mixed at a mass ratio of 85:14:1 and blended for about half an hour using a gentle, shear-free method. The resulting fluorinated polymer mixture did not contain component C, and its standard specific gravity was about 2.03 g / cm 3 The average molecular weight of the perfluoroalkyl ethyl acrylate mixture is less than 1000, the melting point is less than 30°C, and the distribution of the perfluoroalkyl groups is 10% C4, 60% C6, and 30% C8. The fluorine-containing polymer mixture obtained in Example 7 is marked as mixture E2.

[0125] Example 8

[0126] A fluorine-containing polymer mixture was prepared by the method of Example 7, wherein component A was selected from component A3 obtained in Example 3, and the obtained fluorine-containing polymer mixture did not contain component C, and its standard specific gravity was about 2.02 g / cm3 The fluorine-containing polymer mixture obtained in Example 8 is marked as mixture E3.

[0127] Comparative Example 4

[0128] The fluorine-containing polymer mixture was prepared by the method of Example 7, wherein component A was selected from component A'1 obtained in Comparative Example 1, and the obtained fluorine-containing polymer mixture did not contain component C, and its standard specific gravity was about 2.04 g / cm 3 , marked as mixture E'2.

[0129] Example 9

[0130] Component A2 obtained in Example 2, the perfluoroalkyl ethyl acrylate mixture, component C2 obtained in Example 5, and cumene hydroperoxide (CAS: 80-15-9) were mixed at a mass ratio of 65:11:23:1, and blended for about half an hour using a gentle non-shearing method to obtain a fluorine-containing polymer mixture having a standard specific gravity of about 1.83 g / cm 3 The average molecular weight of the perfluoroalkyl ethyl acrylate mixture is less than 1000, the melting point is less than 35°C, and the distribution of the perfluoroalkyl groups is 10% C4, 30% C6, 50% C8, and 10% C10. The fluorine-containing polymer mixture obtained in Example 9 is marked as mixture E4.

[0131] Comparative Example 5

[0132] The fluorine-containing polymer mixture was prepared by the method of Example 9, wherein component A was selected from A'1 obtained in Comparative Example 1, and the specific gravity of the obtained fluorine-containing polymer mixture was about 1.84 g / cm 3 , labeled as mixture E'3.

[0133] Example 10

[0134] Component A2 obtained in Example 1, a perfluoroalkylethyl acrylate mixture, isodecyl acrylate (CAS: 1330-61-6), and cumene hydroperoxide (CAS: 80-15-9) were mixed at a mass ratio of 78:10:11:1, and blended for about half an hour using a gentle non-shearing method to obtain a fluorine-containing polymer mixture having a standard specific gravity of about 1.97 g / cm 3 The average molecular weight of the perfluoroalkyl ethyl acrylate mixture is less than 1000, the melting point is less than 35° C., and the distribution of the perfluoroalkyl groups is 10% C4, 60% C6, and 30% C8. The fluorine-containing polymer mixture obtained in Example 10 is marked as mixture E5.

[0135] Comparative Example 6

[0136] The fluorine-containing polymer mixture was prepared by the method of Example 10, wherein component A was selected from A'2 obtained in Comparative Example 2, and the standard specific gravity of the obtained fluorine-containing polymer mixture was 1.97 g / cm 3 , marked as mixture E'4.

[0137] Preparation of high moisture permeability and ultra-breathable microporous membrane using fluorinated polymer mixture

[0138] Embodiment 11

[0139] The mixed material E1 obtained in Example 6 was pre-pressed into a cylindrical paste-like mixture;

[0140] The paste mixture is extruded into a rod shape by a push press at about 70°C, and then rolled into a ribbon-shaped mixture with a thickness of about 0.45 mm and a width of about 180 mm;

[0141] The strip-shaped mixture is rapidly stretched longitudinally by about 4 times at about 130°C, then rapidly stretched transversely by about 12 times at about 180°C, and finally shaped at about 370°C for about 11 seconds to obtain a highly moisture-permeable and ultra-breathable microporous membrane, marked as M1.

[0142] The thickness of the highly breathable and ultra-permeable microporous membrane M1 is about 0.037mm, the width is about 1800mm, and the specific gravity is about 15g / m 2 , porosity is about 82-85%, tensile strength is greater than 20MPa, air permeability is about 3.9mm / s under 300Pa air pressure, and moisture permeability is about 11000g / m 2 / d.

[0143] Comparative Example 7

[0144] A highly moisture permeable and super breathable microporous membrane was prepared with reference to Example 11, wherein the fluorine-containing polymer mixture was selected as E'1 obtained in Comparative Example 3, and the obtained highly moisture permeable and super breathable microporous membrane was marked as M'1.

[0145] The thickness of the highly breathable and ultra-permeable microporous membrane M'1 is about 0.036mm, the width is about 1800mm, and the specific gravity is about 15g / m 2 , porosity is about 80-83%, tensile strength is greater than 20MPa, air permeability is about 3.6mm / s under 300Pa air pressure, and moisture permeability is about 8000g / m 2 / d.

[0146] The test results of Example 11 and Comparative Example 7 show that the moisture permeability of the microporous membrane M1 prepared from the fluorine-containing polymer mixture containing fluorine-containing ion exchange resin is much greater than that of the microporous membrane M'1 prepared from the fluorine-containing polymer mixture not containing fluorine-containing ion exchange resin. However, the increase in moisture permeability does not impair its air permeability, which is a technical effect that was unpredictable in the prior art.

[0147] Example 12

[0148] The mixed material E2 obtained in Example 7 was pre-pressed into a cylindrical paste-like mixture;

[0149] The paste mixture is extruded into a rod shape by a push press at about 70°C, and then rolled into a ribbon-shaped mixture with a thickness of about 0.45 mm and a width of about 180 mm;

[0150] The strip-shaped mixture is rapidly stretched longitudinally by about 4 times at about 140°C, then rapidly stretched transversely by about 12 times at about 190°C, and finally shaped at about 370°C for about 11 seconds to obtain a highly moisture-permeable and ultra-breathable microporous membrane, marked as M2.

[0151] The thickness of the highly breathable and ultra-permeable microporous membrane M2 is about 0.031mm, the width is about 1800mm, and the specific gravity is about 15g / m 2 , porosity is about 86-89%, tensile strength is greater than 25MPa, air permeability is about 4.8mm / s under 300Pa air pressure, and moisture permeability is about 9200g / m 2 / d.

[0152] Example 13

[0153] A highly moisture permeable and super breathable microporous membrane was prepared with reference to Example 12, wherein the fluorine-containing polymer mixture was the mixture E3 obtained in Example 8, and the obtained moisture permeable and super breathable microporous membrane was marked as M3.

[0154] The thickness of the highly breathable and ultra-permeable microporous membrane M3 is about 0.030mm, the width is about 1800mm, and the specific gravity is about 15g / m 2 , porosity is about 88-90%, tensile strength is greater than 25MPa, air permeability is about 5.6mm / s under 300Pa air pressure, and moisture permeability is about 13500g / m 2 / d.

[0155] Comparative Example 8

[0156] A highly moisture permeable and super breathable microporous membrane was prepared with reference to Example 12, wherein the fluorine-containing polymer mixture was the mixture E'2 obtained in Example 4, and the obtained moisture permeable and super breathable microporous membrane was marked as M'2.

[0157] The thickness of the highly breathable and ultra-permeable microporous membrane M'2 is about 0.031mm, the width is about 1800mm, and the specific gravity is about 15g / m 2 , porosity is about 86-89%, tensile strength is greater than 25MPa, air permeability is about 4.6mm / s under 300Pa air pressure, and moisture permeability is about 8500g / m 2 / d.

[0158] The test results of Examples 12, 13 and Comparative Example 8 show that the moisture permeability of the microporous membranes M2 and M3 prepared from the fluorine-containing polymer mixture containing fluorine-containing ion exchange resin is much greater than that of the microporous membrane M'2 prepared from the fluorine-containing polymer mixture not containing fluorine-containing ion exchange resin, and within a reasonable range of the fluorine-containing ion exchange resin content, the moisture permeability of the microporous membrane will increase with the increase of its content; however, the increase in the moisture permeability of the microporous membrane does not significantly damage its air permeability, which is a technical effect that was unpredictable in the prior art.

[0159] Embodiment 14

[0160] A highly moisture permeable and super breathable microporous membrane was prepared with reference to Example 12, wherein the fluorine-containing polymer mixture was the mixture E4 obtained in Example 9, and the obtained highly moisture permeable and super breathable microporous membrane was marked as M4.

[0161] The thickness of the highly breathable and ultra-permeable microporous membrane M4 is about 0.038mm, the width is about 1800mm, and the specific gravity is about 16g / m 2 The porosity is about 79-82%, the air permeability is about 3.8mm / s under 300Pa air pressure, and the moisture permeability is about 10500g / m 2 / d.

[0162] Comparative Example 9

[0163] A highly moisture permeable and super breathable microporous membrane was prepared with reference to Example 12, wherein the fluorine-containing polymer mixture was the mixture E'3 obtained in Comparative Example 5, and the obtained highly moisture permeable and super breathable microporous membrane was marked as M'3.

[0164] The thickness of the highly breathable and ultra-permeable microporous membrane M'3 is about 0.039mm, the width is about 1800mm, and the specific gravity is about 16g / m 2 The porosity is about 76-80%, the air permeability is about 3.3mm / s under 300Pa air pressure, and the moisture permeability is about 7600g / m 2 / d.

[0165] The test results of Example 14 and Comparative Example 9 show that the moisture permeability of the microporous membrane M4 prepared from the fluorine-containing polymer mixture containing fluorine-containing ion exchange resin is much greater than that of the microporous membrane M'3 prepared from the fluorine-containing polymer mixture not containing fluorine-containing ion exchange resin. However, the increase in moisture permeability does not impair its air permeability, which is a technical effect that was unpredictable in the prior art.

[0166] Embodiment 15

[0167] The mixed material E5 obtained in Example 10 was pre-pressed into a cylindrical paste-like mixture;

[0168] The paste mixture is extruded into a rod shape by a push press at about 70°C, and then rolled into a ribbon-shaped mixture with a thickness of about 0.45 mm and a width of about 180 mm;

[0169] The strip-shaped mixture is rapidly stretched longitudinally by about 4 times at about 140°C, then rapidly stretched transversely by about 12 times at about 190°C, and finally shaped at about 370°C for about 12 seconds to obtain a highly moisture-permeable and ultra-breathable microporous membrane, marked as M5.

[0170] The thickness of the highly breathable and ultra-permeable microporous membrane M5 is about 0.032mm, the width is about 1800mm, and the specific gravity is about 15g / m 2 The porosity is about 86-89%, the tensile strength is greater than 20MPa, the air permeability is about 5.2mm / s under 300Pa air pressure, and the moisture permeability is about 12000g / m 2 / d.

[0171] Comparative Example 10

[0172] A highly moisture permeable and super breathable microporous membrane was prepared with reference to Example 15, wherein the fluorine-containing polymer mixture was the mixture E'4 obtained in Comparative Example 6, and the obtained highly moisture permeable and super breathable microporous membrane was marked as M'4.

[0173] The thickness of the highly breathable and ultra-permeable microporous membrane M'4 is about 0.030mm, the width is about 1800mm, and the specific gravity is about 16g / m 2 The porosity is about 79-82%, the tensile strength of the membrane is greater than 20MPa, the air permeability is about 6.8mm / s at 300Pa air pressure, and the moisture permeability is about 15000g / m 2 / d.

[0174] The test results of Example 15 and Comparative Example 10 show that the moisture permeability of the microporous membrane M'4 prepared from the fluorine-containing polymer mixture whose content of fluorine-containing ion exchange resin exceeds the reasonable range is greater than that of the microporous membrane M5 prepared from the fluorine-containing polymer mixture whose content of fluorine-containing ion exchange resin is within the reasonable range. However, while the moisture permeability increases, its air permeability increases significantly, which leads to a decrease in its waterproof performance. Therefore, only when the content of fluorine-containing ion exchange resin is within a reasonable range can the moisture permeability be effectively improved without affecting its waterproof performance, and the moisture permeability and waterproof performance of the microporous membrane are taken into account, and a technical effect that is unpredictable in the prior art is obtained.

[0175] Preparation of composite materials using high moisture permeability and ultra-breathable microporous membrane

[0176] Example 16

[0177] The highly moisture permeable and ultra-breathable microporous membrane M1 obtained in Example 11 was compounded with nylon 6 plain woven fabric by point-shaped polyurethane bonding adhesive, wherein the surface density of nylon 6 plain woven fabric is 96 g / m 2, a high moisture permeability and ultra-breathable microporous membrane composite material was obtained, marked as F1.

[0178] The initial water pressure resistance of the highly permeable and ultra-breathable microporous membrane composite material F1 is greater than 200 kPa. After being washed 10 times, the water pressure resistance is still greater than 100 kPa. The initial membrane surface oil resistance is level 7. After being washed 10 times, the membrane surface oil resistance is still level 6. The air permeability is about 3.2 mm / s under 300 Pa air pressure, and its moisture permeability (calcium chloride, positive cup method) is about 9500 g / m 2 / d; The sealing effect of the water stop strip at the sewing line is good, and all performance indicators meet the standards for waterproof and breathable clothing fabrics.

[0179] Comparative Example 11

[0180] A high moisture permeability super breathable microporous membrane composite material was prepared with reference to Example 16, wherein the high moisture permeability super breathable microporous membrane was selected from the high moisture permeability super breathable microporous membrane M'1 obtained in Comparative Example 7, and the obtained high moisture permeability super breathable microporous membrane composite material was marked as F'1;

[0181] The initial water pressure resistance of the highly permeable and ultra-breathable microporous membrane composite material F'1 is greater than 200kPa. After being washed 10 times, the water pressure resistance is still greater than 100kPa. The initial membrane surface oil resistance is level 7. After being washed 10 times, the membrane surface oil resistance is still level 6. The air permeability is about 2.8mm / s under 300Pa air pressure, and its moisture permeability (calcium chloride, positive cup method) is about 7000g / m 2 / d; The sealing effect of the water stop strip at the sewing line is good, but the moisture permeability is poor.

[0182] It can be seen from the test results of Example 16 and Comparative Example 11 that the moisture permeability of the microporous membrane composite material F1 prepared from the fluorine-containing polymer mixture containing fluorine-containing ion exchange resin is much greater than that of the microporous membrane composite material F'1 prepared from the fluorine-containing polymer mixture not containing fluorine-containing ion exchange resin. However, the increase in moisture permeability does not impair its water pressure resistance, which is a technical effect that was unpredictable in the prior art.

[0183] Embodiment 17

[0184] A high moisture permeability super breathable microporous membrane composite material was prepared with reference to Example 16, wherein the high moisture permeability super breathable microporous membrane was selected as the high moisture permeability super breathable microporous membrane M2 obtained in Example 12, and the obtained high moisture permeability super breathable microporous membrane composite material was marked as F2;

[0185] The initial water pressure resistance of the highly permeable and ultra-breathable microporous membrane composite material F2 is greater than 200kPa. After being washed 10 times, the water pressure resistance is still greater than 150kPa. The initial membrane surface oil resistance is level 8. After being washed 10 times, the membrane surface oil resistance is still level 7. The air permeability is about 4.3mm / s under 300Pa air pressure, and its moisture permeability (calcium chloride, positive cup method) is about 8300g / m2 / d; The sealing effect of the water stop strip at the sewing line is good, and all performance indicators meet the standards for waterproof and breathable clothing fabrics.

[0186] Embodiment 18

[0187] A high moisture permeability super breathable microporous membrane composite material was prepared with reference to Example 16, wherein the high moisture permeability super breathable microporous membrane was selected as the high moisture permeability super breathable microporous membrane M3 obtained in Example 13, and the obtained high moisture permeability super breathable microporous membrane composite material was marked as F3;

[0188] The initial water pressure resistance of the highly permeable and ultra-breathable microporous membrane composite material F3 is greater than 200kPa. After being washed 10 times, the water pressure resistance is still greater than 150kPa. The initial membrane surface oil resistance is level 8. After being washed 10 times, the membrane surface oil resistance is still level 7. The air permeability is about 5.1mm / s under 300Pa air pressure, and its moisture permeability (calcium chloride, positive cup method) is about 12500g / m 2 / d; The sealing effect of the water stop strip at the sewing line is good, and all performance indicators meet the standards for waterproof and breathable clothing fabrics.

[0189] Comparative Example 12

[0190] A high moisture permeability super breathable microporous membrane composite material was prepared with reference to Example 16, wherein the high moisture permeability super breathable microporous membrane was selected from the high moisture permeability super breathable microporous membrane M'2 obtained in Comparative Example 8, and the obtained high moisture permeability super breathable microporous membrane composite material was marked as F'2;

[0191] The initial water pressure resistance of the highly permeable and ultra-breathable microporous membrane composite material F'2 is greater than 200kPa. After being washed 10 times, the water pressure resistance is still greater than 150kPa. The initial membrane surface oil resistance is level 8. After being washed 10 times, the membrane surface oil resistance is still level 7. The air permeability is about 4.1mm / s under 300Pa air pressure, and its moisture permeability (calcium chloride, positive cup method) is about 7500g / m 2 / d; The sealing effect of the water stop strip at the sewing line is good, and all performance indicators meet the standards for waterproof and breathable clothing fabrics.

[0192] From the test results of Examples 17, 18 and Comparative Example 12, it can be seen that the moisture permeability of the microporous membrane composite materials F2 and F3 prepared from the fluorine-containing polymer mixture containing fluorine-containing ion exchange resin is much greater than that of the microporous membrane composite material F'2 prepared from the fluorine-containing polymer mixture not containing fluorine-containing ion exchange resin. However, the increase in moisture permeability does not impair the water pressure resistance, which is a technical effect that was unpredictable in the prior art.

[0193] Embodiment 19

[0194] A high moisture permeability super breathable microporous membrane composite material was prepared with reference to Example 16, wherein the high moisture permeability super breathable microporous membrane was selected as the high moisture permeability super breathable microporous membrane M4 obtained in Example 14, and the obtained high moisture permeability super breathable microporous membrane composite material was marked as F4;

[0195] The initial water pressure resistance of the highly permeable and ultra-breathable microporous membrane composite material F4 is greater than 200kPa. After being washed with water 10 times, the water pressure resistance is still greater than 100kPa. The initial membrane surface oil resistance is level 7. After being washed with water 10 times, the membrane surface oil resistance is still level 5. The tensile strength is greater than 20MPa, and the air permeability is about 3.5mm / s under 300Pa air pressure. Its moisture permeability (calcium chloride, positive cup method) is about 9600g / m 2 / d; The sealing effect of the water stop strip at the sewing line is good, and all performance indicators meet the standards for waterproof and breathable clothing fabrics.

[0196] Comparative Example 13

[0197] A high moisture permeability super breathable microporous membrane composite material was prepared with reference to Example 16, wherein the high moisture permeability super breathable microporous membrane was selected as the high moisture permeability super breathable microporous membrane M'3 obtained in Comparative Example 9, and the obtained high moisture permeability super breathable microporous membrane composite material was marked as F'3;

[0198] The initial water pressure resistance of the highly permeable and ultra-breathable microporous membrane composite material F'3 is greater than 200kPa. After being washed with water 10 times, the water pressure resistance is still greater than 100kPa. The initial membrane surface oil resistance is level 7. After being washed with water 10 times, the membrane surface oil resistance is still level 5. The tensile strength is greater than 20MPa, and the air permeability is about 2.9mm / s under 300Pa air pressure. Its moisture permeability (calcium chloride, positive cup method) is about 6800g / m 2 / d; The sealing effect of the water stop strip at the sewing line is good.

[0199] The test results of Example 19 and Comparative Example 13 show that the moisture permeability of the microporous membrane composite material F4 prepared from a fluorine-containing polymer mixture containing a fluorine-containing ion exchange resin is much greater than that of the microporous membrane composite material F'3 prepared from a fluorine-containing polymer mixture not containing a fluorine-containing ion exchange resin. However, the increase in moisture permeability does not impair its water pressure resistance, which is a technical effect that was unpredictable in the prior art.

[0200] Embodiment 20

[0201] A high moisture permeability super breathable microporous membrane composite material was prepared with reference to Example 17, wherein the high moisture permeability super breathable microporous membrane was selected as the high moisture permeability super breathable microporous membrane M5 obtained in Example 15, and the obtained high moisture permeability super breathable microporous membrane composite material was marked as F5;

[0202] The initial water pressure resistance of the highly permeable and ultra-breathable microporous membrane composite material F5 is greater than 200kPa. After being washed 10 times, the water pressure resistance is still greater than 100kPa. The initial membrane surface oil resistance is level 7. After being washed 10 times, the membrane surface oil resistance is still level 6. The tensile strength is greater than 20MPa, and the air permeability is about 4.8mm / s under 300Pa air pressure. Its moisture permeability (calcium chloride, positive cup method) is about 11000g / m 2 / d; The sealing effect of the water stop strip at the sewing line is good, and all performance indicators meet the standards for waterproof and breathable clothing fabrics.

[0203] Comparative Example 14

[0204] A high moisture permeability super breathable microporous membrane composite material was prepared with reference to Example 16, wherein the high moisture permeability super breathable microporous membrane was selected from the high moisture permeability super breathable microporous membrane M'4 obtained in Comparative Example 10, and the obtained high moisture permeability super breathable microporous membrane composite material was marked as F'4;

[0205] The initial water pressure resistance of the highly permeable and ultra-breathable microporous membrane composite material F'4 is greater than 200kPa. After being washed 10 times, the water pressure resistance is less than 100kPa. The initial oil resistance of the membrane surface is level 7. After being washed 10 times, the oil resistance of the membrane surface is still level 6. The air permeability is about 6.1mm / s under 300Pa air pressure, and its moisture permeability (calcium chloride, positive cup method) is about 13500g / m 2 / d; The sealing effect of the water stop strip at the sewing line is good, and the air permeability and moisture permeability are extremely excellent, but its water pressure resistance does not meet the standards for waterproof and breathable clothing fabrics.

[0206] The test results of Example 20 and Comparative Example 14 show that the moisture permeability of the microporous membrane composite material F'4 prepared from the fluorine-containing polymer mixture whose content of fluorine-containing ion exchange resin exceeds the reasonable range is greater than that of the microporous membrane composite material F5 prepared from the fluorine-containing polymer mixture whose content of fluorine-containing ion exchange resin is within the reasonable range. However, while the moisture permeability increases, the water pressure resistance performance decreases significantly, which does not meet the standard of waterproof and breathable clothing fabrics. Therefore, only when the content of fluorine-containing ion exchange resin is within a reasonable range can the moisture permeability of the microporous membrane composite material be effectively improved without affecting its waterproof performance, and the moisture permeability and waterproofness of the microporous membrane composite material be taken into account, and a technical effect that is unpredictable in the prior art can be obtained.

[0207] The fluorine-containing polymer mixture disclosed in the embodiment of the present application is obtained by mixing a composition consisting of component A, component B, component C and component D by non-shear mixing, wherein the mass content of each component is 50-90%, 3-25%, 0-35%, 0-3% in sequence, and component A has a standard specific gravity of 2.13-2.18 g / m 3A blend of a high molecular weight polytetrafluoroethylene homopolymer or copolymer dispersion resin and a fluorine-containing ion exchange resin, wherein the mass ratio of the fluorine-containing ion exchange resin to the high molecular weight polytetrafluoroethylene homopolymer or copolymer dispersion resin is 0.5 to 10:100; the fluorine-containing ion exchange resin can effectively improve the moisture permeability of the microporous membrane prepared by the fluorine-containing polymer mixture without damaging its waterproof performance, and the initial moisture permeability of the high moisture permeability super breathable microporous membrane prepared by the fluorine-containing polymer mixture is greater than 10000g / m 2 / d, the air permeability is greater than 2mm / s under 300Pa air pressure difference, the initial oil resistance is at least level 5, it can resist high water pressure, and can prevent toxic and harmful liquids from invading the human body, its air permeability and moisture permeability are better than the existing technology, and the sealing effect at the sewing line is good. High moisture permeability super breathable microporous membrane composite material has high water pressure resistance, high air permeability and high moisture permeability, and has good protection against penetrating toxic and harmful liquids. The protective clothing made of high moisture permeability super breathable microporous membrane composite material is light, comfortable, warm, and has excellent protective performance, which can greatly improve the protective combat capability of operators.

[0208] The technical solutions disclosed in this application and the technical details disclosed in the embodiments are merely illustrative of the inventive concept of this application and do not constitute a limitation on the technical solutions of this application. Any non-creative changes, substitutions or combinations of the technical details disclosed in this application have the same inventive concept as this application and are within the protection scope of the claims of this application.

Claims

1. A fluorine-containing polymer mixture for a highly moisture-permeable and ultra-breathable microporous membrane, characterized in that: A composition consisting of component A, component B, component C and component D is obtained by non-shear mixing, wherein the mass content of each component is 50-90%, 3-25%, 0-35% and 0-3% in sequence; The component A has a standard specific gravity of 2.13-2.18 g / m 3 A blend of a high molecular weight polytetrafluoroethylene homopolymer or copolymer dispersion resin and a fluorine-containing ion exchange resin, wherein the mass ratio of the fluorine-containing ion exchange resin to the high molecular weight polytetrafluoroethylene homopolymer or copolymer dispersion resin is 0.5 to 10:100; wherein the polymer side chain of the fluorine-containing ion exchange resin contains an ion exchange group, and the fluorine-containing ion exchange resin is a fluorine-containing and chlorine-containing sulfonic acid -SO3H conductive polymer; The preparation method of the fluorine-containing and chlorine-containing sulfonic acid-SO3H conductive polymer comprises: A fluorine-containing sulfonyl fluoride liquid phase monomer is mixed with a gas phase mixed monomer, and polymerized to obtain a fluorine-containing chlorine-containing conductive polymer emulsion; wherein the total weight ratio of the fluorine-containing sulfonyl fluoride liquid phase monomer to the gas phase mixed monomer is 4:5, and the fluorine-containing sulfonyl fluoride liquid phase monomer is formed by mixing 70% by weight of CF2=CF-OCF2CF(CF3)-O-CF2CF2-SO2F and 30% by weight of CF2=CF-O-CF2CF2-SO2F; and the gas phase mixed monomer is composed of 90% tetrafluoroethylene and 10% chlorotrifluoroethylene in a molar ratio; The obtained fluorine-containing and chlorine-containing conductive polymer emulsion is hydrolyzed by sulfonyl fluoride -SO2F to obtain a fluorine-containing and chlorine-containing conductive polymer with sulfonic acid -SO3H; The component B is a fluorinated alkyl acrylate monomer or a fluorinated alkyl methacrylate monomer or a mixture of the two, having a molecular weight of less than 3000 and a melting point of less than 80°C; The component C is a polyurethane acrylate prepolymer or a fluorine-free alkyl acrylate monomer or a mixture of the two, with a molecular weight of less than 8000 and a melting point below 80°C; Component D is a high temperature free radical initiator.

2. The fluorine-containing polymer mixture for high moisture permeability and super breathable microporous membrane according to claim 1, characterized in that: The high molecular weight polyethylene homopolymer or copolymer dispersion resin is an ultra-high molecular weight polytetrafluoroethylene homopolymer or copolymer dispersion resin, and its standard specific gravity is 2.135-2.165 g / m 3 The melting point is between 325 and 350°C.

3. The fluorine-containing polymer mixture for high moisture permeability and super breathable microporous membrane according to claim 1, characterized in that: The mass contents of component A, component B, component C and component D are 65-80%, 6-15%, 2-23% and 0-2% respectively.

4. The fluorine-containing polymer mixture for a highly moisture-permeable and ultra-breathable microporous membrane according to claim 1, characterized in that: The component B includes: perfluorobutyl ethyl acrylate, perfluorobutyl ethyl methacrylate, perfluorohexyl ethyl acrylate, perfluorohexyl ethyl methacrylate, perfluorooctyl ethyl acrylate, perfluorooctyl ethyl methacrylate, N-methyl perfluorobutyl sulfonyl amino ethyl acrylate, N-methyl perfluorobutyl sulfonyl amino ethyl methacrylate, N-methyl perfluorohexyl sulfonyl amino ethyl acrylate, N-methyl perfluorohexyl sulfonyl amino ethyl methacrylate, N-methyl perfluorooctyl sulfonyl amino ethyl acrylate, and N-methyl perfluorooctyl sulfonyl amino ethyl methacrylate.

5. The fluorine-containing polymer mixture for high moisture permeability and super breathable microporous membrane according to claim 1, characterized in that: The polyurethane acrylate prepolymer is hot-melt, and its melting point is less than 80° C. The raw materials for its preparation include: Aromatic diisocyanates, aliphatic diisocyanates; Polyols with molecular weight between 600 and 5000; Wherein, the polyol includes polyethylene glycol, polypropylene glycol, polybutylene glycol, polyester polyol or polycarbonate polyol.

6. The fluorine-containing polymer mixture for a highly moisture-permeable and ultra-breathable microporous membrane according to claim 5, characterized in that: The preparation method of the polyurethane acrylate prepolymer comprises: The reactor was evacuated to remove moisture, diisocyanate was added, the temperature was raised, and stirring was started; The temperature in the reaction kettle rises to 50-150°C, and a polyol is introduced into the kettle, and the reaction is carried out for 10-180 minutes; the polyol is a polyether polyol or a polyester polyol, wherein the molar ratio of diisocyanate to polyol is 2:1-8:1; Add hydroxyalkyl acrylate or hydroxyalkyl methacrylate into the reaction kettle to completely react with the unreacted isocyanate by hydroxyalkyl, maintain the reaction temperature at 50-150°C, react for 10-180 minutes, cool and discharge the material, and obtain a polyurethane acrylate prepolymer; wherein the molar number of the added hydroxyalkyl acrylate or hydroxyalkyl methacrylate is greater than or equal to the molar number of the unreacted isocyanate.

7. The fluorine-containing polymer mixture for a highly moisture-permeable and ultra-breathable microporous membrane according to claim 1, characterized in that: The fluorine-free alkyl acrylate is a monomer that can be polymerized by free radicals or a mixed monomer thereof, including: hydroxyalkyl acrylate, hydroxyalkyl methacrylate, C5-C20 alkyl acrylate, C4-C20 alkyl methacrylate, and C6-C20 vinyl ester; wherein the hydroxyalkyl acrylate includes hydroxyethyl acrylate or hydroxypropyl acrylate, and the hydroxyalkyl methacrylate includes hydroxyethyl methacrylate or hydroxypropyl methacrylate.

8. The fluorine-containing polymer mixture for high moisture permeability and super breathable microporous membrane according to claim 1, characterized in that: The half-life of the high-temperature free radical initiator is measured at a temperature between 100 and 250° C., and specifically includes diisopropylbenzene peroxide, 2,5-dimethyl-2,5-bis-tert-butylperoxyhexane, di-tert-butyl peroxide, 2,5-dimethyl-2,5-bis-tert-butylperoxide-3-hexyne, and cumene hydroperoxide.

9. The use of the fluorine-containing polymer mixture for high moisture permeability and super breathable microporous membrane according to any one of claims 1 to 8, characterized in that: The fluorine-containing polymer mixture is used to prepare a highly moisture-permeable and ultra-breathable microporous membrane, and the preparation method specifically includes: Component A, component B, component C and component D are mixed in a set ratio, and blended for a first set time by a gentle non-shearing method to obtain a fluorine-containing polymer mixture; Pre-pressing the fluorine-containing polymer mixture into a cylindrical paste mixture; Extruding the paste mixture into a rod shape at a first set temperature, and then rolling it into a ribbon-shaped mixture; The strip-shaped mixed material is quickly stretched longitudinally at a second set temperature, then quickly stretched transversely at a third set temperature, and finally fixed at a fourth set temperature for a second set time, thereby obtaining a highly moisture-permeable and ultra-breathable microporous membrane.

Citation Information

Patent Citations

  • Double-resistant polytetrafluoroethylene microporous membrane

    CN102294181A

  • Highly-oil-repellenting highly-waterproof seamless polytef expansion sheet materials and preparation method thereof

    CN103158310A

  • Preparation method of super-hydrophobic polytetrafluoroethylene microporous membrane, membrane prepared by preparation method and application of super-hydrophobic polytetrafluoroethylene microporous membrane

    CN104437126A

  • Preparation method of polytetrafluoroethylene waterproof moisture-permeable fabric with high moisture permeability

    CN104760381A

  • Fluorine-containing and chlorine-containing conductive macromolecule single-side-filled composite film and preparation method thereof

    CN106977640A